Penerapan Metode Entropy dan Grey Relational Analysis dalam Evaluasi Kinerja Karyawan - Setiawansyah, Setiawansyah (Journal of Data Science and Information Systems, 2024)
Employee performance evaluation is an important process in human resource management that aims to assess the achievement, progress, and contribution of an employee to organizational goals. The problem that occurs in employee performance evaluation is that there is no method used in evaluating employee performance, but in the evaluation of performance appraisal carried out there are already criteria used for employee performance appraisal. This study uses the Grey Relational Analysis method in evaluating employee performance appraisals and the Entropy method for weighting criteria. The results of employee performance rank 1 with a final GRA value of 0.1638 was obtained by Kusnanto employees, rank 2 with a final GRA value of 0.1546 was obtained by Hariawan employees, rank 3 with a final GRA value of 0.1502 was obtained by Yoseph employees.